Sonochemical synthesis of hydroxyapatite nanoparticles with different precursor reagents - (:unkn) unknown (Polish Academy of Sciences, 2012)
Different precursor chemicals (3Ca(OH)2, Ca(NO3) 2 and CaO as Ca2+ sources, H3PO4 and (NH4)2HPO4 as PO43- sources were used to synthesis of nanosized hydroxyapatite powder with ultrasonic precipitation method. The effect of different chemical precursors was investigated. Sample characterization was achieved by powder X-ray diffraction, the Fourier transformed infrared transmission spectroscopy, zeta sizer, scanning electron microscopy, density and surface area measurements.